The Influence Of Regional Financial Independence Ratio, Dependence Ratio And Effectiveness Ratio On Allocation Of Capital Expenditures To Government In North Sumatra - Atika Almasshadrina; Irawan (Yayasan Multidimensi Kreatif, 2025)
This research aims to analyze the influence of Regional Financial Independence and Regional Expenditure Management on Financial Performance. The sample used in this research was 33 local governments. The observation period used in this research was 5 years so the number of observations in this research was 165 observation sample units. The data obtained were analyzed using statistical formulas, namely by using panel data analysis which was processed using the SPSS 19 program. The results of the partial analysis showed that the t-count value was 0.138 < 1.97 (t-table) and sig was 0.890 > 0.05, so H1 is rejected and H0 is accepted, it can be concluded that the regional financial independence ratio does not have a partially significant effect on the allocation of regional spending in Regency and City governments in North Sumatra. 2,721 > 1.97 (t-table) and sig 0.007 < 0.05, so H2 is accepted and H0 is rejected, it can be concluded that the regional dependency ratio has a partially significant effect on regional expenditure allocation in Regency and City governments in North Sumatra. The t-count value is 2.802 > 1.97 (t-table) and sig 0.006 < 0.05, so H3 is accepted and H0 is rejected, it can be concluded that the ratio has a significant partial effect on effectiveness on regional expenditure allocation in Regency and City governments in North Sumatra..